CREATION OF AN INTERACTIVE DIGITAL SYSTEM BASED ON MOBILE APPLICATIONS FOR PREVENTION OF CARIES IN CHILDREN WITH DIABETES (The New Uzbekistan Journal of Medicine, 2026)
This article analyzes the issues of preventing dental caries in children with diabetes mellitus. The effectiveness of an interactive digital system based on a mobile application was studied. The research was conducted among diabetic children aged 7–12 years, comparing their oral health condition before and after the use of the mobile application. The results demonstrated that the use of the mobile app significantly reduced the risk of dental caries and improved oral hygiene among diabetic children.